A ubiquitous bone marrow reservoir of preexisting SARS-CoV-2-reactive memory CD4+ T lymphocytes in unexposed individuals - Li, Jinchan; Reinke, Simon; Shen, Yu; Schollmeyer, Lena; Liu, Yuk-Chien; Wang, Zixu; Hardt, Sebastian; Hipfl, Christian; Hoffmann, Ute; Frischbutter, Stefan; Chang, Hyun-Dong; Alexander, Tobias; et al. (Frontiers in Immunology, 2022)
Circulating, blood-borne SARS-CoV-2-reactive memory T cells in persons so far unexposed to SARS-CoV-2 or the vaccines have been described in 20-100% of the adult population. They are credited with determining the efficacy of the immune response in COVID-19. Here, we demonstrate the presence of preexisting memory CD4+ T cells reacting to peptides of the spike, membrane, or nucleocapsid proteins of SARS-CoV-2 in the bone marrow of all 17 persons investigated that had previously not been exposed to SARS-CoV-2 or one of the vaccines targeting it, with only 15 of these persons also having such cells detectable circulating in the blood. The preexisting SARS-CoV-2-reactive memory CD4+ T cells of the bone marrow are abundant and polyfunctional, with the phenotype of central memory T cells. They are tissue-resident, at least in those persons who do not have such cells in the blood, and about 30% of them express CD69. Bone marrow resident SARS-CoV-2-reactive memory CD4+ memory T cells are also abundant in vaccinated persons analyzed 10-168 days after 1°-4° vaccination. Apart from securing the bone marrow, preexisting cross-reactive memory CD4+ T cells may play an important role in shaping the systemic immune response to SARS-CoV-2 and the vaccines, and contribute essentially to the rapid establishment of long-lasting immunity provided by memory plasma cells, already upon primary infection.